RNA-Seq based transcriptome analysis during bovine viral diarrhoea virus (BVDV) infection - Liu, Cun; Liu, Yanhan; Liang, Lin; Cui, Shangjin; Zhang, Yanming (BMC genomics, 2019)
Bovine viral diarrhoea virus (BVDV) is the member of the genus Pestivirus within the Flaviviridae family and responsible for severe economic losses in the cattle industry. BVDV can employ 'infect-and-persist' strategy and 'hit-and-run' strategy to remain associated with hosts and thus contributes to BVDV circulation in cattle herds. BVDV have also evolved various strategies to evade the innate immunity of host. To further understand the mechanisms by which BVDV overcomes the host cell innate immune response and provide more clues for further understanding the BVDV-host interaction, in this descriptive study, we conducted a investigation of differentially expressed genes (DEGs) of the host during BVDV infection by RNA-Seq analysis. Our analysis identified 1297, 1732, 3072, and 1877 DEGs in the comparison groups mock vs. MDBK cells infected with BVDV post 2 h (MBV2h), mock vs. MBV6h, mock vs. MBV12h, and mock vs. MBV24h, respectively. The reproducibility and repeatability of the results were validated by RT-qPCR. Enrichment analyses of GO annotations and KEGG pathways revealed the host DEGs that are potentially induced by BVDV infection and may participate in BVDV-host interactions. Protein-protein interaction (PPI) network analyses identified the potential interactions among the DEGs. Our findings suggested that BVDV infection induced the upregulation of genes involved in lipid metabolism. The expression of genes that have antiviral roles, including ISG15, Mx1, OSA1Y, were found to be downregulated and are thus potentially associated with the inhibition of host innate immune system during BVDV infection. The expression levels of F3, C1R, KNG1, CLU, C3, FB, SERPINA5, SERPINE1, C1S, F2RL2, and C2, which belong to the complement and coagulation signalling cascades, were downregulated during BVDV infection, which suggested that the complement system might play a crucial role during BVDV infection. In this descriptive study, our findings revealed the changes in the host transcriptome expression profile during BVDV infection and suggested that BVDV-infection induced altering the host's metabolic network, the inhibition of the expression of antiviral proteins and genes within the complement system might be contributed to BVDV proliferation. The above findings provided unique insights for further studies on the mechanisms underlying BVDV-host interactions.